Manajemen Fisioterapi Pada Pasien Post Reconstruction Anterior Cruciatum Ligament (ACL) Fase III : A Case Report - Rifkah Aliyah (Nur Science Institute, 2022)
The stability of the knee joint during rotational movement so that excessive translation does not occur in the tibia and femur is the main function of the anterior cruciate ligament (ACL). This ligament is frequently injured and must be reconstructed to restore stability to the knee, reducing the risk of re-injury in order to return to sports safely. The purpose of this case report is to provide information regarding the appropriate physiotherapy exercise program in phase III post ACLR. A 38-year-old man who has a hobby of playing soccer has injured his ACL and has undergone ACL reconstruction in June 2021. When the post-ACLR examination was carried out, it had entered its 9th week and therapy was carried out for 4 weeks. The results showed that after carrying out 6 treatments in 4 weeks there was a significant change in passive knee dextra ROM. But there is no change in edema and there is no hypertrophy of the quadriceps and gastrocnemius muscles. The increase in functional activity as measured using the lower extremity functional scale (LEFS) showed an increase in activity standing for 1 hour and walking as far as 1 mile. Strength deficits and post-ACL reconstruction muscle atrophy, especially in the quadriceps muscles, can be overcome by incorporating a program of closed kinetic and open kinetic chain exercises as well as isometric exercises. Despite a rehabilitation program, the mechanical strength of the ACL does not fully return to normal